Impacts of rotary swaging on the deformation behavior of conventionaland 3D-printing Inconel 718 superalloy - Benč, Marek; Izák, Josef; Walek, Josef; Opěla, Petr; Kopeček, Jaromír (Springer Nature, 2025)
This study compares the hot deformation behavior of Inconel 718 superalloy manufactured by the conventional and 3D-printing technology. The effect of subsequent intensive plastic deformation on changes in deformation behavior is also investigated. Both the nickel superalloys prepared by the conventional and 3D-printing ways before and after post-processing by rotary swaging were subjected to uniaxial hot compression tests to characterize a corresponding deformation behavior (via flow stress response) at a temperature range of 900-1200 degrees C and a strain rate range of 0.1-100 s-1. Slightly different results were obtained at lower strain rates and temperatures. It was further also observed the conventionally prepared specimen way unable to withstand deformation at a temperature of 1200 degrees C, whereas the specimen using the 3D-printing technology was able to withstand deformation at this temperature range. Microstructure analysis showed that the rotary swaging process applied to 3D printed had a significant effect on grain size refinement and microstructure development with compared to conventionally prepared specimen. The average grain size of the 3D-printed workpiece after rotary swaging process was less than 2 mu m. Furthermore, with decreasing deformation temperature and increasing strain rate, the Vickers microhardness measurement showed an increasing microhardness. Subsequent intensive plastic deformation resulted in relatively slight increase in both the flow stress response and microhardness. Maximum values of flow stress response (approximately 710 MPa) and microhardness (approximately 420 HV) were achieved at a combination temperature of 900 degrees C and strain rate of 10 s-1.
Keywords: 3D printing; Inconel 718 superalloy; Rotary swaging; Hot compression test; Microstructure; Flow stress response; Hot deformation behavior